(untitled)
The purpose of this paper is to introduce a new structure of bipolar soft topology called bipolar soft minimal structure. Later, we present most important operators in bipolar soft minimal spaces such as m -interior, m -closure and m -boundary. Moreover, we define m -separated bipolar soft sets and bipolar soft m -connected sets. Furthermore, we introduce a new concept of bipolar soft minimal spaces called bipolar soft minimal connected. We prove that the bipolar soft intersection of a pair of bipolar soft m -connected spaces over the common universal set is a bipolar soft m -connected space. In addition, we show that bipolar soft m -connected space is not a bipolar soft m -hereditary property. Also, we discuss some relations, properties and results of these new concepts of bipolar soft minimal spaces. Finally, some counterexamples are provided. , number=2, journal=European Journal of Pure and Applied Mathematics, year=2025, month=May, pages=5928